IMPLIKASI PSIKOLOGIS PERNIKAHAN USIA DINI STUDI KASUS DI KELURAHAN KARANG TARUNA KECAMATAN PELAIHARI KABUPATEN TANAH LAUT - Harpani Matnuh, Refqi Alfina, Zainul Akhyar, dan (Lambung Mangkurat University Indonesia, 2016)
Marriage is one of the basic principles of life are the most important in the association or a perfect society, and marriage is not only one of the very precious to regulate domestic life and descent, but also can be seen as one way to the introduction between a people with Other people that it would be a way to deliver aid between one another of course implementation must be based on the rules that have been determined. Therefore, the marriage took place with the aim of forming a family (household) are happy and prosperous. For that husband and wife should help each other and complementary, so that each can develop a personality that is aligned so that it will achieve material prosperity and spiritual. In psychology marriage or marriage is a transition period of transition from childhood to adulthood, which begins with puberty. seen psychologically, marriage someone who is still not quite of age or under age will certainly have an impact that might be a trauma, because of unpreparedness run developmental tasks that arise after the wedding while in capability and maturity themselves have not been able to undergo an obligation or duty the-duty.